The Bright Fluorescent Protein mNeonGreen Facilitates Protein Expression Analysis In Vivo. Issue 2 (1st February 2017) - Hostettler, Lola; Grundy, Laura; Käser-Pébernard, Stéphanie; Wicky, Chantal; Schafer, William R; Glauser, Dominique A
Abstract: The Green Fluorescent Protein (GFP) has been tremendously useful in investigating cell architecture, protein localization, and protein function. Recent developments in transgenesis and genome editing methods now enable working with fewer transgene copies and, consequently, with physiological expression levels. However, lower signal intensity might become a limiting factor. The recently developed mNeonGreen protein is a brighter alternative to GFP in vitro . The goal of the present study was to determine how mNeonGreen performs in vivo in Caenorhabditis elegans —a model used extensively for fluorescence imaging in intact animals. We started with a side-by-side comparison between cytoplasmic forms of mNeonGreen and GFP expressed in the intestine, and in different neurons, of adult animals. While both proteins had similar photostability, mNeonGreen was systematically 3–5 times brighter than GFP. mNeonGreen was also used successfully to trace endogenous proteins, and label specific subcellular compartments such as the nucleus or the plasma membrane. To further demonstrate the utility of mNeonGreen, we tested transcriptional reporters for nine genes with unknown expression patterns. While mNeonGreen and GFP reporters gave overall similar expression patterns, low expression tissues were detected only with mNeonGreen. As a whole, our work establishes mNeonGreen as a brighter alternative to GFP for in vivo imaging in a multicellular organism. Furthermore, the present research illustrates the utility of mNeonGreen to tag proteins, mark subcellular regions, and describe new expression patterns, particularly in tissues with low expression.